Commentaries on the four last books of Moses arranged in the form of a harmony - Calvin, Jean (Printed for the Calvin Translation Society, 1847)
v.1-2. Genesis. -- v.3-6. Pentateuch. -- v.7. Joshua. -- v.8-11. Psalms. -- v.12-14. Isaiah. -- v.15-19. Jeremiah and Lamentations. -- v.20-21. Ezekiel. -- v.22-23. Daniel. -- v.24-28. Minor prophets. -- v.29-30. Gospel of John. -- v.31-33. Harmony of the Gospels. -- v.34-35. Acts. -- v.36. Romans. -- v.37-38. Corinthians. -- v.39. Philippians, Colossians, Thessalonians. -- v.40. Hebrews. -- v.41. Timothy, Titus, Philemon. -- v.42. Catholic epistles.